Waste-driven construction: A state-of-the-art review on the integration of waste in 3D printed concrete in recent researches for sustainable development - Murali G.; Wong L.S. (Elsevier Ltd, 2025)
The concrete 3D printing sector can advance sustainable development by formulating environmentally-friendly materials incorporating waste as supplementary cementitious materials. Addressing the high cement content in printed materials is crucial for the sustainability of this rapidly evolving technology in concrete digital fabrication. This article comprehensively explores utilizing waste materials in 3D-printing concrete. This literature review encompasses discussions on various waste materials to formulate 3D printable compositions. It explores the chemical properties and microstructure of these raw materials and their impact on the rheological and mechanical properties of the resulting mixtures. Additionally, the literature review includes discussions on X-ray diffraction and scanning electron microscopy analyses, focusing on their applications in examining the microstructure. Environmental sustainability aspects related to these materials are also reviewed and discussed. This review offers a novel perspective on using waste materials in 3D printing, which is not extensively covered in existing literature. The incorporation of various waste materials significantly impacts the construction process of 3D-printing by altering key properties, including rheological and mechanical properties. These properties varied depending on the type of waste material used. The study demonstrates that the compressive strength of 3D-printed concrete is significantly influenced by the type of waste materials incorporated and the orientation of the printed specimens. Including waste in 3D-printing concrete reduces carbon emissions and energy consumption compared to using pure ordinary Portland cement mixtures. The review paper is significant as it highlights the potential for waste materials in 3D-printed concrete to promote environmental sustainability by reducing cement usage, improving mechanical properties, and decreasing carbon emissions and energy consumption, while offering a comprehensive analysis of the chemical and microstructural effects of these materials. ? 2024 Elsevier Ltd